Cooperative Learning of 4C Skills and the Use of Digital Media Towards Students' Academic Attitudes - Mohd. Sahrul Niizam Sahidin; Muhamad Suhaimi Taat (2020)
This study was conducted to identify the influence of cooperative learning of students 4c skills (communication, collaboration, critical and creative thinking) and the use of digital media by teachers towards students’ academic attitudes in History subjects.The respondents consisted of 400 Form 4 students of 18 daily secondary schools in the Kota Kinabalu district.The design of this study is a non-experiment that used a quantitative approach through survey method.The instrument used for this study is through questionnaires with Likert scale measurement.The data obtained is analyzed in descriptive and inferential using SPSS 25 software.The results of the findings shown that the use of digital media by teachers was at a moderate level.Meanwhile, there was no significant difference in the use of digital media by teachers between male and female students.However, there was a weak significant relationship between the use of digital media by teachers with students’ academic attitudes.Further implications and suggestions were discussed.